Analysis of Terminal Retributions on Genuine Income The Regency of Central Buton - Hastuti, Hastuti; Katjina, Husna (Institute for Research and Community Service, 2022)
The study aims to determine the contribution of the Wamengkoli Wara terminal levy to regional income from 2018 to 2022. This research uses a qualitative method. Qualitative research is a type of research whose findings are not obtained by statistics or other forms of calculation. This research was conducted by collecting data in reasonable circumstances. The data sources used are primary and secondary data sources. The techniques used in data collection are interviews, observation and documentation. Retribution analysis is used in data analysis. The sampling method uses a saturated sample over a 5-year period, or from 2018 to 2022. The study findings show that: Between 2018 and 2022, the average wamengkoli wara terminal levy on local revenue was 1.63 percent. In general, passengers who travel back and forth have private vehicles that are not billed at the terminal in Buton Tengah Regency, which is still a new expansion area, so the volume of terminal service users is still lacking.